2017
DOI: 10.1111/vsu.12688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orthopedic reinforced gloves versus double standard gloves on contamination events during small animal orthopedic surgery

Abstract: Surgeons reluctant to double glove due to perceptions of decreased dexterity and discomfort may safely opt for wearing orthopedic gloves, which may improve their compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…However, this glove is recommended as an over glove in a double glove technique, which was not performed in this study . In human medicine, a significant decrease in perforation rate has been seen when a double latex glove is used vs a single latex glove, but recent large‐scale, randomized trials have determined that there is no statistically significant difference in perforation rate between orthopedic gloves and double latex gloves during TPLO and other clean orthopedic procedures . This evidence, in conjunction with the lack of recommendation of use by the CDC and WHO to decrease SSI, led the authors to omit the use of a double glove or single glove technique from the revised protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, this glove is recommended as an over glove in a double glove technique, which was not performed in this study . In human medicine, a significant decrease in perforation rate has been seen when a double latex glove is used vs a single latex glove, but recent large‐scale, randomized trials have determined that there is no statistically significant difference in perforation rate between orthopedic gloves and double latex gloves during TPLO and other clean orthopedic procedures . This evidence, in conjunction with the lack of recommendation of use by the CDC and WHO to decrease SSI, led the authors to omit the use of a double glove or single glove technique from the revised protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, SSI risk has also been shown to increase with increasing wound contamination (with the lowest incidence associated with clean and the highest reported for dirty wounds) . In addition, the odds of a glove perforation have been shown to increase with surgical time as well as with the invasiveness of the procedure . Although glove perforations tend to occur more commonly in the nondominant hand, there appears to be no difference with regard to surgeon experience (board‐certified vs resident) …”
Section: Managing Risks Associated With Surgical Site Infectionsmentioning
confidence: 99%
“…To reduce the likelihood of a glove failure during a surgical procedure, surgeons often double glove or use reinforced gloves, particularly during orthopedic procedures. In a recent randomized control trial, no difference was found in contamination events (glove failures) between double gloving and the use of reinforced gloves, suggesting that surgeon comfort and dexterity can drive glove selection (either double glove or reinforced gloves) without compromising patient care.…”
Section: Prevention Of Surgical Site Infectionsmentioning
confidence: 99%
“…De ontwikkeling van postoperatieve wondinfecties bij twee honden ondanks perioperatieve toediening van antimicrobiële middelen creased mortality are some of the consequences for patients with an SSI (Kurz et al, 1996;Hayes et al, 2017;Gonzalez et al, 2017). Surgical site infections also result in significantly higher costs for the owner caused by prolonged hospitalization, more intensive postoperative care and frequent control visits (Nicoll et al, 2014).…”
Section: Development Of Surgical Site Infections Despite Perioperativmentioning
confidence: 99%